Planejamento curricular na pandemia da covid 19: relatos de experiências das práticas docentes na EMEI Criança Feliz - ALVES, Maria Marta Marques (2023)
this paper addresses the theme "curriculum planning in the pandemic of covi-19: Reports of experiences of teaching practices in emei happy child ", considering that this situation was a challenge to the routine of teachers who, despite having faced numerous difficulties, made adjustments so that the planning continued to be used as a foundation that supports the pedagogical practices, especially because of the need to adapt the classes remotely. The main objective of this work is to understand how teachers who work in early childhood education reorganized the curriculum planning in pandemic times in their teaching practices on the emergency remote teaching in the periods 2020 and 2021. The specific objectives are to identify how the school has used the curriculum planning in times of pandemic as a means of favoring the emergency remote teaching; to identify how the school Highlight the main challenges for the formulation and use of curriculum planning in times of pandemic of covid 19; Analyze the reports of experiences of pedagogical practices of teachers related to curriculum planning in pandemic times of covid 19 for classes in emergency remote teaching. The study methodology combined bibliographical research and field research with 5 teachers who report experiences as a way to show how planning was elaborated before and during the duration of the pandemic. After the study, it was inferred that in the scientific literature and in the reports of teachers' experiences occurred and, still occur, difficulties in offering a results education through remote teaching, even with technological instruments to elaborate the Curriculum Planning and teach the classes. One fact to be emphasized is the uncertainty that many teachers have regarding the fulfillment of the activities proposed to students in the pandemic period, since it cannot be assured whether the activities were resolved by the students or by the parents of the children.